Gabapentin Monotherapy for Partial Seizures - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1998)
A randomized double-blind trial of gabapentin monotherapy in patients with newly diagnosed partial epilepsy was conducted by an international study group.